The Use Of Electronic Platforms In The Teaching Of Informatics At School - To'rayeva mahtob jalolovna. (Zien Journals, 2024)
This article gives ideas and comments on the role and importance of teaching computer science in schools today as well as the use of electronic platforms.
Keywords: Informatics; information technology; pedagogue; knowledge